Pengaruh Kompensasi dan Iklim Organisasi Terhadap Kepuasan Kerja Serta Dampaknya Pada Kinerja Pendamping Keluarga Harapan - Gilang Bhirawa Noraga; Dadang Sudirno (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
This study aims to determine the magnitude of the effect of compensation received and perceived organizational climate on the work satisfaction of companion in the Family Hope Program, besides this research also aims to determine the effect of job satisfaction on the accompanying performance of the Family Hope Program. The method used in this study is a quantitative method using observational collection techniques, questionnaires and literature. Koesioner was distributed to 46 samples of respondents, then tested the instrument and tested the classic assumption on questionnaire results. In testing hypotheses on research variables, multiple regression analysis and simple regression analysis were used. The results of the study show that there is a partial and positive effect of compensation and organizational climate on job satisfaction, then it is known simultaneously that compensation and organizational climate have a positive and significant effect on job satisfaction, with a strong level of relationship between compensation and organizational climate with job satisfaction. From the results of this study, it is also known that job satisfaction has a positive and significant effect on the accompanying performance of the companion, with a moderate level of relationship between job satisfaction and the accompanying performance of the Family Hope Program.